Private equity and venture capital – theoretical considerations - Drewniak, Zbigniew (Copernican Journal of Finance & Accounting, 2013)
Private equity and venture capital are still recognized as a modern source of companies funding. Studying the literature and some market information we can notice that the terms private equity and venture capital are often treated as synonyms or even confused. The article pointed out the discrepancies referring to the understanding of concepts – private equity and venture capital. It also refers to PE/VC market that can be understand differently what can influence how the statistics data are read.